The symptomatology of cerebrospinal fluid HIV RNA escape: a large case-series. (15th November 2021) - Chan, Terrence Y.-H.; De Zan, Valentina; Gregg, Alistair; Alagaratnam, Jasmini; Gerevini, Simonetta; Antinori, Andrea; D'Arminio Monforte, Antonella; Saracino, Annalisa; Trunfio, Mattia; Everitt, Alex; Rackstraw, Simon; Marta, Monica; et al.
Abstract : Objective: To characterize the clinical, laboratory and radiological characteristics of persons with HIV (PWH) presenting with cerebrospinal fluid (CSF) HIV RNA escape. Design: Retrospective case review of PWH presenting with symptomatic CSF HIV RNA escape at seven tertiary HIV clinical sites in the United Kingdom and Italy. Method: PWH with symptomatic CSF HIV RNA escape episodes were identified and data obtained from medical records. CSF HIV RNA escape was defined as quantifiable CSF HIV RNA in unquantifiable plasma HIV RNA or CSF HIV RNA greater than plasma HIV RNA in cases where plasma HIV RNA was quantifiable. The onset of clinical symptoms was classified as acute (<2 weeks–6 months), or chronic (>6 months) and differences in presentation in those with CSF HIV RNA below and above 1000 copies/ml determined. Results: We identified 106 PWH with CSF HIV RNA escape (65 male); 68 (64%) PWH had acute presentations and 38 (36%) had chronic presentations. Cognitive decline ( n  = 54; 50.9%), confusion ( n  = 20; 18.9%) and headache ( n  = 28; 26.4%) were the most common presentations, with cognitive decline being more common in PWH who presented chronically compared with PWH who presented acutely (73.7% vs. 35.3%, P  = 0.0002). Sixty PWH had CSF HIV RNA at least 1000 copies/ml and presented more frequently with confusion ( n  = 15/60; 25.0%) compared with PWH with CSF HIV RNA less than 1000 copies/ml at presentation ( n  = 5/46; 10.9%; P  = 0.03). Conclusion: Cognitive decline, confusion and headache are the most frequent presenting symptoms of CSF HIV RNA escape and their relative frequency varied according to symptom onset and CSF HIV RNA concentration. Abstract : Supplemental Digital Content is available in the text